Analysis of total biomass, carbon stock and carbon dioxide uptake in Kandelia candel stands - Risti, Saulimita; Sarno; Andarini S., Raras Nidya (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Mangrove ecosystems play a crucial role in mitigating climate change through carbon sequestration. This study aimed to quantify the biomass, carbon stock, and carbon dioxide uptake of Kandelia candel stands on Payung Island, South Sumatra, Indonesia. Methods: Non-destructive sampling was conducted at two stations using 10x10 m plots along 50 m transects. Tree diameter was measured and allometric equations were used to estimate biomass and carbon stocks. Environmental parameters were also recorded. Finding: The highest biomass (193.69 tons/ha), carbon stock (89.11 tons C/ha), and CO2 uptake (320.04 tons CO2/ha) were found at Station II, correlating with larger average tree diameters. Environmental conditions, including salinity (0‰), pH (7.0), temperature (24-28°C), and humidity (90-91%), were favorable for K. candel growth. The substantial carbon storage demonstrates the importance of these stands for climate change mitigation. Conclusion: This study provides valuable data on the carbon sequestration potential of K. candel in a unique estuarine setting, contributing to our understanding of mangrove ecosystems' role in global carbon cycles and informing conservation strategies. Novelty/Originality of this Study: This study focuses on quantifying the biomass, carbon stocks, and CO₂ uptake of Kandelia candel stands within the unique estuarine ecosystem of Payung Island, South Sumatra. By providing species-specific data on K. candel—a mangrove species that has been relatively underexplored—this research addresses a significant knowledge gap and enhances our understanding of its role in carbon sequestration.